Review Laporan Keuangan Baznas Kabupaten Magelang dengan PSAK 109 - Fuad Yanuar; Yassirly Amriya; Nuwun Priyono (Jurnal Akuntansi dan Pajak, 2020)
The National Amil Zakat Agency (BAZNAS) is the official and only body formed by the government based on Presidential Decree No. 8 of 2001 which has the duties and functions of collecting and distributing zakat, infaq, and alms (ZIS) at the national level. BAZNAS is declared as a non-structural government institution that is independent and is responsible to the President through the Minister of Religion. Thus, BAZNAS together with the Government is responsible for overseeing the management of zakat which is based on: Islamic law, trust, expediency, justice, legal certainty, integrated and accountability. PSAK 109 is one of the financial standards set for the amil zakat body which is expected to realize reporting uniformity and simplicity of recording. So that the public can read the zakat manager's accounting reports and oversee their management so that muzzaki believes in channeling zakat through the amil zakat body. This condition occurs in BAZNAS Magelang Regency which has presented the report well. PSAK 109 consists of five components, namely the cash flow statement report, balance sheet (statement of financial position), report on changes in funds, statement of assets under management and notes to financial statements. This research uses applied research with a qualitative approach. This research was conducted in four stages, namely data collection conducted by interviews and documentation, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the financial recording system at BAZNAS Magelang Regency is in accordance with PSAK 109.